1986
DOI: 10.1007/bf02140783
|View full text |Cite
|
Sign up to set email alerts
|

Psychological adjustment in a college-level program of marked academic acceleration

Abstract: The questionnaire responses of 24 markedly accelerated young students were compared with those of 24 regular-aged university students, 23 National Merit Scholars, and 27 students who had qualified for acceleration but instead elected to participate in high school. Measures included the Minnesota Multiphasic Personality Inventory, California Psychological Inventory, the Tennessee Self-Concept Scale, and the Inventory of Parent and Peer Attachment. Accelerated students differed minimally from the college-aged gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 8 publications
0
25
0
1
Order By: Relevance
“…Janos et al (1988) reported no detrimental effects of acceleration on young entrants to college. In another study, Robinson and Janos (1986) found similar adjustment patterns for early entrants in comparison to three equally able nonaccelerated comparison groups, noting only unconventionality as a distinguishing characteristic of the early entrants. A study of female-only early college entrants, positive personality growth was found during the first year of acceleration in the program (Cornell, Callahan, & Loyd, 1991).…”
Section: Content Accelerationmentioning
confidence: 52%
“…Janos et al (1988) reported no detrimental effects of acceleration on young entrants to college. In another study, Robinson and Janos (1986) found similar adjustment patterns for early entrants in comparison to three equally able nonaccelerated comparison groups, noting only unconventionality as a distinguishing characteristic of the early entrants. A study of female-only early college entrants, positive personality growth was found during the first year of acceleration in the program (Cornell, Callahan, & Loyd, 1991).…”
Section: Content Accelerationmentioning
confidence: 52%
“…Many authors have attempted to allay these personality adjustment concerns by pointing out the failure of previous research efforts to detect substantial social or emotional problems among early college entrants (Brody, Lupkowski, & Stanley, 1988;Pollins, 1983;Robinson & Janos, 1986;Stanley & Benbow, 1983). However, the failure to find evidence of adjustment problems is not persuasive if studies do not employ rigorous methods of personality assessment and an appropriate design (Cornell, Callahan, Bassin, & Ramsey, 1991).…”
mentioning
confidence: 99%
“…Several studies have employed standard personality assessment measures (Pollins, 1983;Robinson & Janos, 1986). Pollins (1983) administered the California Psychological Inventory (CPI) and several other instruments to 21 eariy college entrants prior to early college entrance and compared them to three nonaccelerant groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They usually have better psychological adjustment then their average peers (Janos & Robinson, 1985;Robinson & Janos, 1986). The implications of this fact for career development are several.…”
Section: Gifted Girlsmentioning
confidence: 96%